2002
DOI: 10.2355/isijinternational.42.779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Precipitation Kinetics in High-Cr Ferritic Steels.

Abstract: Precipitation strengthening is important to improve creep strength of heat resisting steels at elevated temperatures. Especially, in the high-Cr ferritic steels recently developed for Ultra Super Critical Power Plants, precipitation behavior is complicated and should be clarified because the correlation between various strengthening factors are still not well understood. In this study, we focus on the change in precipitation behavior of MX type carbonitrides in model steels with different heat treatment condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…12) MX particles Ta or V-rich were also reported for normalized ORNL RA steels, tempered at 750°C. 7) These three types of morphologies, including in some cases the "wing" morphology, have been observed in 9CrMoVNb, 13) 9CrWCoVNb 14) and CrWNb 15) steels after tempering but, to our knowledge, the "wing" morphology involving Ta and V has not been reported in other alloys of composition similar to Eurofer97, such as F82H or JLF1. On the other hand, "duplex" precipitates, in which many TaC particles precipitate on a rectangular TiN particle were found for the F82H RA steel.…”
Section: Morphology and Compositionmentioning
confidence: 91%
“…12) MX particles Ta or V-rich were also reported for normalized ORNL RA steels, tempered at 750°C. 7) These three types of morphologies, including in some cases the "wing" morphology, have been observed in 9CrMoVNb, 13) 9CrWCoVNb 14) and CrWNb 15) steels after tempering but, to our knowledge, the "wing" morphology involving Ta and V has not been reported in other alloys of composition similar to Eurofer97, such as F82H or JLF1. On the other hand, "duplex" precipitates, in which many TaC particles precipitate on a rectangular TiN particle were found for the F82H RA steel.…”
Section: Morphology and Compositionmentioning
confidence: 91%
“…This is typical feature of precipitation strengthening of matrix with fine MX in the advanced heat resisting steels. 10) Although total amount of MX type carbonitrides increased in Co free steel as shown in Fig. 4(b), they were localized inside d-ferrite region as exemplified in Fig.…”
Section: Effect On Creep Properties By Microstructuralmentioning
confidence: 97%
“…Therefore, extensive research have been conducted on precipitates in conjunction with creep strength property of ferritic creep resistant steels. [6][7][8][9][10][11][12][13][14][15][16] It is well known that fine MX carbonitride is stable at elevated temperatures and plays an important role in improving creep strength. 6) Recently, it has been reported that a precipitation of Zphase in a form of Cr(Nb, V)N occurs after long-term exposure at elevated temperatures in the niobium added high chromium ferritic creep resistant steels.…”
Section: Introductionmentioning
confidence: 99%